Capabilities Without Rights? The Trespassing Project in Naples - Lavinia Bifulco; Raffaele Monteleone; Carlotta Mozzana (Social Work and Society, 2012)
The aim of this paper is to analyze a project for young NEET in southern Italy in terms of capabilities. Our objective is to examine to what extent it is possible to promote capabilities for work, for voice and for education in a context of lack of resources and rights as the one the project is rooted in.